Prevalence and levels of serum antibodies to gram negative microorganisms in Turkish patients with HLA-B27 positive acute anterior uveitis and controls - (:unkn) unknown (TAYLOR & FRANCIS INC, 2006)
Purpose: Acute anterior uveitis (AAU), seronegative spondyloarthropathies such as ankylosing spondylitis and reactive arthritis form the group of HLA-B27-associated diseases. The aim of this study was to analyze the prevalence and levels of serum antibodies against gram negative bacteria in Turkish patients with AAU. Methods: Twenty-five patients each with previously diagnosed HLA-B27 positive and negative AAU and 25 age- and sex-matched healthy control subjects were included in the study. Serum IgM, IgG and IgA antibodies to Yersiniae enterocolitica, Campylobacter jejuni and Chlamydia trachomatis were measured using enzyme linked immunosorbent assay (ELISA). Categorical data were analyzed by chi-square test. Serum levels were analyzed using the Kruskal-Wallis test. Results: The prevalence of serum IgM, IgG and IgA antibodies did not differ significantly between the HLA-B27 positive AAU, HLA-B27 negative AAU and control groups with the exception of serum IgA antibodies against Yersiniae enterocolitica. IgA antibody against Yersiniae enterocolitica was found to be more frequently positive in the control group. Comparison of serum IgM, IgG and IgA antibody levels did not significantly differ between three groups. Conclusions: Serum antibody positivity against Yersiniae enterocolitica, Campylobacter jejuni and Chlamydia trachomatis is not frequent in the HLA-B27 positive and negative AAU patients. Serum levels of IgM, IgG, and IgA antibodies also did not show significant difference between three groups. No association between these microorganisms and the etiology of AAU was evident.
Keywords: acute anterior uveitis; gram negative microorganisms; HLA-B27; ANKYLOSING-SPONDYLITIS; YERSINIA INFECTION; REACTIVE ARTHRITIS; CLINICAL-FEATURES; IMMUNE-RESPONSE; KLEBSIELLA; BACTERIA; SPONDYLOARTHROPATHIES; OUTBREAK; PATTERNS